Psychotherapy and politics international: A personal and professional introduction. (February 2017) - Minikin, Karen
Abstract: This article introduces a new Associate Editor. The author's heritage, international life experience and career reflect the influence of diversity and relational connection in a world that continues to struggle with the politics and psychology of alienation.